Charging up the mining industry : feasibility of battery powered underground mining equipment - Heino, Konsta (My University, 2019)
The mining industry is at a turning point where customers are expressing significant interest towards battery and electrically powered underground mining equipment as an alternative for mainstream diesel powered mining equipment. Especially battery electric vehicles (BEV) have gained a lot of attraction from customers due to their potential as an environmentally friendly alternative for diesel as well as due to their potential cost saving ability through reduced ventilation requirements inside underground mines. However, due to the relatively new and expensive technologies involved in BEVs, their acquisition costs in comparison to diesel are expected to be significantly higher and as the level of potential cost savings is still unclear, there are questions surrounding the feasibility of BEVs in mining. Therefore, this study is conducted in order to determine their feasibility and to investigate the potential business opportunity surrounding battery powered mining equipment, especially in the United States and Canada, which are expected to be their largest potential markets. This study is conducted as commissioned research for a global supplier of underground mining equipment. By design this research was done as an intensive single case study, which attempts to investigate the business opportunity in a business to business environment with the help of existing literature on customer value management and total cost of ownership. The main data collection for this study was conducted through a questionnaire, which took place at the assigning company’s workshop. In addition, two interviews were done as supportive data collection. The study suggested that there definitely is a feasible business opportunity for battery powered mining equipment in the United States and Canada. Customers expressed a clear interest and desire towards battery powered equipment and the study showed that long-run cost savings will help justify the opportunity cost of acquiring battery powered mining equipment.
Keywords: customer value management, total cost of ownership, feasibility study, case study